ANALISIS KINERJA KEUANGAN BANK SYARIAH DALAM PENERAPAN PRINSIP-PRINSIP SYARIAH - Yasmin Safa Annisa (Jurnal Ekonomi Syariah Darussalam, 2026)
This study aims to analyze the financial performance of Islamic banks in implementing Sharia principles in Indonesia. The study employed a descriptive qualitative method using a literature review approach. The data were obtained from Islamic bank annual reports, Financial Services Authority (OJK) statistics, regulations, fatwas issued by the National Sharia Council–Indonesian Ulema Council, and relevant scientific journals. The findings show that Islamic banking experienced positive growth during the 2021–2023 period, as indicated by increases in total assets, third-party funds, financing distribution, and profitability ratios, namely Return on Assets (ROA) and Return on Equity (ROE). Liquidity, measured by the Financing to Deposit Ratio (FDR), remained in a healthy category, while the Capital Adequacy Ratio (CAR) indicated strong capital conditions. The implementation of Sharia principles, including the prohibition of riba, gharar, and maysir, as well as the values of justice, transparency, and prudence, does not hinder the financial performance of Islamic banks. Instead, Sharia compliance can increase public trust, maintain financial stability, and support the sustainable growth of Islamic banking. Keywords: Financial Performance, Islamic Banks, Profitability, Liquidity